A comparative analysis of weekly internal and external workloads between starting and non-starting professional soccer players: A retrospective 21-week examination - Kunz, P.; Düking, P.; Sperlich, B. (PLOS ONE, 2024)
Objectives Aims of the present investigation encompassed: (i) the quantification of training and match loads experienced by starters and non-starters within a professional soccer team; (ii) the identification of variations in these loads across different training modalities, namely, Preparation Training (PT), Match and Match Compensation Training (M&MCT), and their cumulative sum (Total Load; TL); and (iii) the formulation of guidelines aimed at harmonizing the weekly workloads between the groups.